ADVANCES IN THE DIAGNOSIS OF HEAD AND NECK CANCERS: AN OVERVIEW OF CONTEMPORARY METHODS AND TECHNOLOGIES - Anita Janda, (International Journal of Innovative Technologies in Social Science, 2025)
Diagnostics of head and neck cancers have rapidly advanced in recent years due to improvements in imaging, endoscopic techniques, molecular diagnostics and digital technologies. New tools including narrow-band imaging (NBI), advanced PET/CT and PET/MR modalities, radiomics, next generation sequencing (NGS), and liquid biopsy assays (ctDNA, HPV-cfDNA) have enhanced detection sensitivity, localisation accuracy and disease monitoring. Artificial intelligence and machine learning are integrating imaging and molecular data, enabling early biomarkers and refined therapy selection. This review synthesises major advances from 2020–2025 in head and neck cancer diagnostics and outlines future research priorities.